Implementasi ERP Odoo dengan Modul Akuntansi pada SMK PGRI 3 Bogor - Masri, Indah; Oktrivina, Amelia; Astuti, Shinta Budi; Murni, Yetty; Musta'ani, Salis; Ambarwati, Sri; Terminanto, Agung; Rasyid, Diandra Kamila (PROGRESIF: Jurnal Pengabdian Komunitas Pendidikan, 2025)
Vocational education in Vocational High Schools (SMK) has an important role in preparing skilled human resources, especially in facing the era of the Industrial Revolution 4.0. This Community Service (PKM) activity aims to introduce and train students of SMK PGRI 3 Bogor in implementing the Enterprise Resource Planning (ERP) ODOO system, especially in the accounting module. The methods used in this activity include lectures, discussions, practices, and evaluations. The results of the activity showed that students experienced an increase in understanding of the concept of ERP and its application in accounting. The evaluation questionnaire showed that 83% of respondents agreed that the material presented was in accordance with their needs. It is hoped that this activity can continue and provide further benefits in information technology training in other schools. Through a better understanding of ERP, students are expected to be able to develop relevant skills and compete in an increasingly digital world of work.